Online 3D Terrain Visualization: Implementation and Testing - Che Mat, Ruzinoor; A.R.M., Shariff; Mahmud, A.R.; Pradhan, B. (Asian Network for Scientific Information, 2011)
Geographical Information Systems (GIS) and three dimensional (3D) World Wide Web (WWW) applications usage are on the rise.The demand for online 3D terrain visualization has increased not just for cartographers, geographers, geologists and psychologists but also popular among the ordinary people.The aim of study was to determine that how online 3D terrain visualization could be employed using the most appropriate GIS software by finding the applicable web sewer to launch the system.The Virtual Reality Markup Language (VRML) was used as the file format for visualizing 3D terrain in online environments.For that purpose, two experiments were conducted in these studies. First experiment involved the comparison of VRML output from four different GIS software in terms of terrain visualization quality (bad, acceptable, better) and data file size (VRML original, VRML compress and image).The technique of 3D terrain draped with satellite imageries was involved in these experiments.The Arc GIs 9.2 software was found to be the best GIS software which produced promising results with high quality of terrain visualization.Second experiment involved on finding the best web sewers by comparing four selected web servers at different locations for launching the system online.The Spatial Research Group web sewer which is located close to the testing environment found to be the best.This is because it has the best value and fastest time for most of the tests being done.Therefore, these findings are useful in guiding the developers to choose the most suitable GIS software for developing online 3D terrain visualization.It is also could assists the developers to choose the applicable web sewer for the development of online 3D terrain visualization.